Kewenangan Kepolisian Dalam Penegakan Hukum Pidana Terhadap Pelaku Prostitusi Online - Rusmana, I Putu Edi (Morality: Jurnal Ilmu Hukum; Vol 10 No 2 (2024): Morality : Jurnal Ilmu Hukum, 2024)
Online prostitution is a crime that is growing rapidly, the emergence of the internet has made the crime of prostitution develop through electronic media, especially social media. The development of the internet is one of the main reasons for the development of criminal acts. The internet is easily accessible, providing space for prostitution service providers to develop their prostitution business into the digital world. There is a need for extra handling from law enforcement, namely the police, through their authority to take action and enforce criminal law against perpetrators of online prostitution. Through investigative actions, investigations, arrests are the domain of the police in enforcing criminal law. Thus, the focus of the problem that the author writes about in this research is how is the criminal law that regulates online prostitution in Indonesia? and how is law enforcement carried out by the Indonesian Police against perpetrators of online prostitution in Indonesia? The purpose of writing is to be able to clearly understand the criminal law regulations governing online prostitution and law enforcement carried out by the Indonesian Police against perpetrators of online prostitution in Indonesia. The existence of statutory regulations can become a reference for the police in taking firm action and providing appropriate criminal sanctions for perpetrators of online prostitution crimes now and in the future. The first conclusion that can be drawn from this research is that the regulation of prostitution is regulated in Articles 298 and 506 of the Criminal Code, in the ITE Law it is regulated in Article 27 paragraph (1) and criminal sanctions are regulated in Article 45. The second conclusion is the enforcement of criminal law for acts Prostitution crime is the authority of the police, through investigations, arrests and investigations of perpetrators of online prostitution crimes, namely pimps only